THE STRATEGIC DEVELOPMENT OF PUGUNG RAHARJO MEGALITHIC PARK USING SWOT ANALYSIS - Niken Paramitasari; Franceda Utama; M. Ariza Eka Yusendra; Lilla Rahmawati; Yan Aditiya Pratama (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Lampung has the potential for tourism and it can be developed on a national or international scale. A varied tourism destination ranging from natural, nautical, agritourism, culture, and artificial tourism make Lampung be an attractive tourism alternative for domestics and foreign tourists. One of the tourism destinations in Lampung Province is a cultural heritage in the megalithic era. It is Pugung Raharjo Megalithic Park in East Lampung. However, the emergence of tourism causes the Pugung Raharjo Megalithic Park to have an imbalance in tourist visits between other tourist destinations in the same district. It is because the quality of tourist destinations is not evenly distributed among one another. The purpose of this study was to measure the strategic development for Pugung Raharjo Megalithic Park by using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The results of the analysis showed that Pugung Rahajo Megalithic Park positioned on Growth Quadran. It explained that it is based on SWOT-4K Matrix, suitable to implement Stable Growth Strategy.Keywords:  SWOT Analysis, Strategic Development, Tourism Destination